PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS V SD NEGERI 12 LANGSA - Angel Karolyn Siagian; Sukirno; Juliati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning motivation is a drive that comes from within and outside students to foster enthusiasm and achieve learning goals. This motivation affects the extent to which students are interested and actively involved in the learning process. This study aims to determine the effect of using Wordwall media on students' learning motivation in IPAS subjects in class V SD Negeri 12 Langsa. This research method uses Experimental Design with Nonequivalent control group design. The sample of this study was 40 students in class V. The test results show that H0 is rejected and Ha is accepted, which means there is an effect of using Wordwall media on students' learning motivation. Thus, it can be concluded that the use of Wordwall media has an effect on the learning motivation of class V students at SD Negeri 12 Langsa. This study recommends the use of Wordwall media as a digital learning evaluation tool to influence students' learning motivation. Therefore, teachers and other researchers can use Wordwall media to improve students' learning motivation.